Theoretical study of the thermochemistry of chlorine oxyfluorides - Sánchez, Hernán Rubén (2016)
There is a lack of experimental thermochemical values for most chlorine oxyfluorides. Previous high level theoretical, CCSD(T), results showed uncommonly large errors in the standard heats of formation calculated through the atomization method. We propose that the differences are due to unusually large contributions to energy from higher excitations within the coupled cluster framework, and we tackle the problem by using a calculation scheme based on isodesmic reactions. Our suspicions are supported by results of static correlation diagnostics. Our final recommended values are in better agreement with the experimental data available. Other thermodynamic properties are also calculated.